Analisa Pelatihan Optimalisasi Konten Visual Marketing Menggunakan Aplikasi Artificial Intelligence (AI) dan Manajemen Keuangan Digital Bagi UMKM Kelurahan Prapatan Kota Balikpapan - Ugroseno Damara Prasadhana Handoyo; Nadya Novalensha; Nur Alwiyani; Chinta Permata Sari; Reni Ramadhan Br Sembiring (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve digital literacy and managerial skills of Micro, Small, and Medium Enterprises (MSMEs) through two training programs: "Optimizing Marketing Content Using Artificial Intelligence (AI) Applications" and "Digital Financial Management." The program was implemented through several stages, including problem identification, training material development, hands-on training, mentoring, and evaluation using pre-test and post-test instruments to measure program effectiveness. Fifteen MSMEs from Prapatan Village, Balikpapan City, participated in the program. The evaluation results showed that the training significantly improved participants' understanding of the use of digital marketing and technology-based financial management. Prior to the training, most participants still had limited digital literacy and had not utilized technology for promotion or financial recording. After participating in the program, 73.3% of participants assessed the material as excellent and relevant to their business needs. This program provides a tangible contribution to the development of technology-based applied science while supporting community economic empowerment through the MSME digitalization process.